Challenges of BCLC stage C hepatocellular carcinoma: Results of a single-institutional experience on stereotactic body radiation therapy. Issue 32 (7th August 2020) - Que, Jenny; Lin, Chia-Hui; Lin, Li-Ching; Ho, Chung-Han
Abstract : Abstract: In this study, we evaluated the feasibility and efficacy of stereotactic body radiation therapy (SBRT) in the treatment of Barcelona Clinic Liver Cancer (BCLC) stage C hepatocellular carcinoma (HCC). This retrospective study evaluated 139 patients with BCLC stage C HCC who underwent CyberKnife SBRT between January 2009 and September 2017. All patients had BCLC-C, Child–Turcotte–Pugh score A-B. In-field control, overall survival (OS), progression free survival (PFS), and prognostic factors were evaluated. An objective response rate was achieved in 81.5% patients (complete response, 36.2%, partial response, 45.3%). The median survival was 15.44 months, and the 1-, 3-, 5-year OS rates were 56%, 28%, and 20%, respectively. The median PFS was 6 months, the PFS rate at 1-, 3-, and 5-year were 35%, 14%, and 10%, respectively. In-field control of 1 to 2 years was achieved in 85.1% of patients. The major pattern of failure was out-field intrahepatic failure which comprised 42.9% of patients. Multivariate analysis revealed that the Child–Turcotte–Pugh score, macrovascular invasion, advance stage (III-IV), and tumor response rate were independent predictors of OS. The result of our study shows that SBRT is a safe and effective therapeutic option for BCLC stage C HCC lesions that are unsuitable for standard loco-regional therapies, Moreover, SBRT has acceptable local control rates and low-treatment toxicity.